FuSM Implementasi Metode Fuzzy State Machine untuk Mengoptimalkan Proses Pengambilan Keputusan dalam Game Verse Seeker: Jurnal Multimedia dan Game Teori - Nova Rahma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2024)
A Fuzzy State Machine (FuSM) serves as the conceptual foundation for enhancing decision-making in Verse Seeker, a game blending artificial intelligence and non-playable characters (NPCs). The research explores the intersection of FSM, Maze Generator, Artificial Intelligence, and the integration of Ayat Al-Qur'an, delving into a novel approach for NPC behavior optimization. The hypothesis posits that incorporating fuzzy logic into the FSM model improves adaptability and decision quality in complex game environments. The methodology involves designing and implementing a hybrid FSM with a maze generator and Quranic verses. Results indicate a substantial enhancement in NPC decision-making, offering a more immersive and dynamic gaming experience. This research contributes to the synergy between AI and game design, showcasing the potential of fuzzy logic applications in refining virtual world interactions. In conclusion, the study underscores the effectiveness of the proposed model in optimizing decision-making within Verse Seeker, opening avenues for further advancements in AI-driven game development.